2020
DOI: 10.1029/2019wr025470
|View full text |Cite
|
Sign up to set email alerts
|

Assessing XMT‐Measurement Variability of Air‐Water Interfacial Areas in Natural Porous Media

Abstract: This study investigates the accuracy and reproducibility of air-water interfacial areas measured with high-resolution synchrotron X-ray microtomography (XMT). Columns packed with one of two relatively coarse-grained monodisperse granular media, glass beads or a well-sorted quartz sand, were imaged over several years, encompassing changes in acquisition equipment, improved image quality, and enhancements to image acquisition and to processing software. For the glass beads, the specific solid surface area (SSSA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
6
12
0
Order By: Relevance
“…The pore-scale study by Gao et al (2021b) showed that the bursting process during Haines jumps induced by rough grain surfaces can significantly increase the capillary-associated (mobile) FIFA at the front. Besides, this finding is also in agreement with Brusseau et al (2009) and consistent with the results of Araujo and Brusseau (2020) for measurements at the steady-state. Implementing a linear regression over the 𝐴𝐴 𝐴𝐴 max 𝑛𝑛𝑛𝑛 − IMGD data we obtain the following relation for the natural sands:…”
Section: Comparison Of Measured Interfacial Area With Literature Datasupporting
confidence: 91%
See 1 more Smart Citation
“…The pore-scale study by Gao et al (2021b) showed that the bursting process during Haines jumps induced by rough grain surfaces can significantly increase the capillary-associated (mobile) FIFA at the front. Besides, this finding is also in agreement with Brusseau et al (2009) and consistent with the results of Araujo and Brusseau (2020) for measurements at the steady-state. Implementing a linear regression over the 𝐴𝐴 𝐴𝐴 max 𝑛𝑛𝑛𝑛 − IMGD data we obtain the following relation for the natural sands:…”
Section: Comparison Of Measured Interfacial Area With Literature Datasupporting
confidence: 91%
“…Most commonly, the fluid-systems used in the reported experiments are air-water and, less often, NAPL-water. To the authors' knowledge there are only four studies that report the measured specific capillary-associated FIFA Table 3 Parameters Applied in the Model to Fit the Experimental Data (Araujo & Brusseau, 2020;Brusseau et al, 2006;Culligan et al, 2006;Porter et al, 2010). XMT was used in each of these studies.…”
Section: Comparison Of Measured Interfacial Area With Literature Datamentioning
confidence: 99%
“…(2020b). The capillary pressure water saturation curve ( P c –S w ) and the specific air–water interfacial area curve (A aw –S w ) measured by various methods were reported in the literature (Araujo & Brusseau, 2020; Araujo et al., 2015; Brusseau et al., 2007). Note that A aw denotes the specific air–water interfacial area in the pore network, which is different from a aw (i.e., the air–water interfacial area in a pore body) in Section 2.…”
Section: Pore‐network Modeling Of Pfas Transport In a Water‐unsaturat...mentioning
confidence: 99%
“…At near water‐saturated conditions, the bulk capillary air–water interfaces are greater than the thin‐water‐film air–water interfaces. As the water saturation decreases, the bulk capillary air–water interfaces first increase and then decrease (Araujo & Brusseau, 2020; Dalla et al., 2002; Kibbey & Chen, 2012; Porter et al., 2009; Reeves & Celia, 1996). Conversely, the thin‐water‐film air–water interfaces increase monotonically as the water saturation decreases and quickly become the dominant air–water interfaces (Brusseau et al., 2007; Costanza‐Robinson & Brusseau, 2002; Kibbey & Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used x‐ray microtomography (µCT) to visualize the movement and distribution of multi‐phase fluids within porous media in three dimensions (e.g., Blunt et al., 2013; Wildenschild & Sheppard, 2013). Traditionally, this methodology has required experiments to be limited to observations under quasi‐equilibrium flow conditions due to the time required to acquire a µCT image (e.g., Araujo & Brusseau, 2020; Costanza‐Robinson et al., 2008; Porter et al., 2010). With the recent advent of fast µCT, it is now possible to conduct non‐equilibrium multi‐phase flow experiments (e.g., Berg et al., 2013; Leu et al., 2014; Meisenheimer, McClure, et al., 2020; Schlüter et al., 2016; Singh et al., 2017).…”
Section: Introductionmentioning
confidence: 99%